Os discursos incentivadores da leitura: uma análise de campanhas contemporâneas em prol dessa prática - Varella, Simone Garavello (2014)
Our research aims to undertake the survey of some representations of contemporary reading practices by analyzing videos to encourage reading posted on the YouTube website. For this analysis we conducted a survey of videos that, by their similarities and differences, allowed us to organize them into two categories (Campaigns and Protocampaigns), whose subdivision was based on our observation of aspects such as the motivation of its production, the strategies of their generic composition (gender campaign), the degree of specialization of its production, and the means of media movement for which these campaigns were originally made. These categories were also divided into two thematic areas, in our view, illustrating how reading is preponderantly represented in these media productions. They are: Who reads, progresses and Who reads, travels . By relying on principles of French Discourse Analysis of and Cultural History of Reading, we will develop our analysis in order to describe any discursive representations that make reading these videos aimed to promote it, as well as describe the representations of reader the producers of these videos make the audience they are targeting. Therefore, in our research we seek to analyze some evidence entered in the production of these videos, projections of reading practices, to reflect on a given imaginary we share today about what reading is, how it should be exercised, than being a good reader, and how to promote it.